Conflict management and its effects: a demonstration to understand employee conflict at the commercial banks in Bangladesh - Chowdhury, N.M. Muhtasim (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.